2020
DOI: 10.1155/2020/3870902
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Oral Solution Prepared from the Ultrasonic Extract of Radix dichroae roots against Eimeria tenella in Broiler Chickens

Abstract: This study was conducted to determine the optimal dose of the oral solution of the ultrasonic extract of Radix dichroae (UERD) and to provide experimental support for a safe clinical dose for anticoccidial treatment of broiler chickens. Radix dichroae root extracts were prepared using the ultrasonic extraction method. The anticoccidial activity of the oral solution prepared from the ultrasonic extract of Radix dichroae roots was tested in broiler chickens following oral infection with a field isolate of E. ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Similarly, Hirani et al [ 37 ] reported that the acute phase of infection had decreased the level of Hb in the infected groups and the values also returned to usual after recovery. Coccidiosis results dysfunction of spleen, leading to acute massive hemorrhage manifested by bloody diarrhea [ 38 ], which might be one of the reasons for a decreased Hb level.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Hirani et al [ 37 ] reported that the acute phase of infection had decreased the level of Hb in the infected groups and the values also returned to usual after recovery. Coccidiosis results dysfunction of spleen, leading to acute massive hemorrhage manifested by bloody diarrhea [ 38 ], which might be one of the reasons for a decreased Hb level.…”
Section: Resultsmentioning
confidence: 99%
“…There are seven Eimeria species affecting chickens, including Eimeria acervulina, Eimeria brunetti, Eimeria maxima, Eimeria mitis, Eimeria necatrix, Eimeria praecox, and Eimeria tenella. The parasites multiply in the intestinal epithelia, destroying the cells and reducing digestive capacity and nutrient absorption in the bird, with Eimeria tenella being highly pathogenic and causing caecal coccidiosis (1)(2)(3)(4)(5). Coccidiosis is responsible for 6-10% of all broiler mortalities, and the annual loss caused by Eimeria infection to the poultry industry is estimated at more than $3 billion (6,7).…”
Section: Introductionmentioning
confidence: 99%